Thermokinetic studies of the process of secondary reduction of silicon carbide materials - Derevyanko , I.V.; O.V., Zhadanos; Yaroshenko , Ya.O.; Nadtochiy , A.A. (Theory and Practice of Metallurgy, 2024)
Purpose: Silicon carbide, a constant leader in the field of ceramic materials with extreme properties, today faces the challenge of sustainable development. Despite a wide range of applications: from the production of abrasive tools, high-temperature heaters, refractory ceramics to metallurgy, traditional methods of SiC production are associated with high energy consumption and a significant environmental footprint. The bulk of silicon carbide is produced in resistance furnaces using the Acheson method. One of the issues in the silicon carbide production process is the low yield of marketable products, which is 15-19% of the load weight. Modern trends in the creation of energy-efficient and environmentally friendly technologies encourage the use of secondary materials. This work investigates the possibility of obtaining metallurgical-grade silicon carbide from waste from electrothermal production, which will reduce the anthropogenic load on the environment and reduce the cost of the final product. Methodology: Laboratory studies of the thermokinetics of the process of secondary silicon carbide reconditioning were conducted, the chemical composition of the resulting silicon carbide-containing product was determined. Results and scientific novelty: The possibilities of secondary materials reconditioning for electrothermal production were investigated. Studies of the obtained silicon carbide-containing materials were conducted. According to the results of the studies, directions for the use of the specified product were determined. Practical value: Utilization of secondary materials will reduce the amount of waste sent to landfills and reduce the risk of environmental pollution by harmful substances. Creation of a closed production cycle: The introduction of secondary raw material processing technologies will contribute to the creation of a closed production cycle, which is one of the key principles of sustainable development.